2020
DOI: 10.24203/ajas.v8i6.6397
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Mortality and Yield-per-recruit of Nile Tilapia (<em>Oreochromis niloticusM/em>) in Garmat Ali River, Iraq

Abstract: The study was conducted to estimate the growth, mortality, recruitment and yield-per-recruit of Oreochromis niloticus from Garmat Ali River, Basrah, Iraq from October 2019 to September 2020. The population parameters were analyzed using the FAO-ICLARM stock assessment tool (FiSAT). A total of 2696 O. niloticus ranged from 7.0 to 25.0 cm and the sizes 13.0-18.0 cm constituted 64.2% of the total catch. The length-weight relationship was W= 0.012L3.109 suggesting that the species shows positive allometric growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, the result of the virtual population analysis (VPA) revealed that the majority of O. niloticus and O. aureus individuals were harvested at lengths 20 cm and 17 cm, respectively. Also, the estimated values for the length at first capture (L50) of O. niloticus and O. aureus in the same river (14.9 and 13.9 cm, respectively) [57,18] were greater than the lengths at first maturity (Lm) of O. aureus, 6.6-9.2 cm and O. niloticus, 7.0-8.0 cm [58,35]. The occurrence of such a situation suggests that individuals of the species get the chance to join the stock before becoming vulnerable to capture by the available fishing gear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the result of the virtual population analysis (VPA) revealed that the majority of O. niloticus and O. aureus individuals were harvested at lengths 20 cm and 17 cm, respectively. Also, the estimated values for the length at first capture (L50) of O. niloticus and O. aureus in the same river (14.9 and 13.9 cm, respectively) [57,18] were greater than the lengths at first maturity (Lm) of O. aureus, 6.6-9.2 cm and O. niloticus, 7.0-8.0 cm [58,35]. The occurrence of such a situation suggests that individuals of the species get the chance to join the stock before becoming vulnerable to capture by the available fishing gear.…”
Section: Discussionmentioning
confidence: 99%